Güncel Hemşirelik Pratikleri - Akcan, Kübra; Turan, Zeliha; Çapuk, Hüseyin; Yiğit, Muhammet Faruk; Yıldırım, Zeynep; Bozcu, Ebru; Doğan, Candan; Atay, Mehmet Emin; Fırat, Mustafa Özkan; Kaplan, Ebubekir; Sir, Özkan; Uçar, Mehmet; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-